NILAI TAMBAH PROSES PENGOLAHAN KOPI ARABIKA SECARA BASAH (WEST INDISCHEE BEREDING) DAN KERING (OST INDISCHEE BEREDING) DI KECAMATAN KINTAMANI, BANGLI - Sembiring, Noveliska Br; Satriawan, I Ketut; Tuningrat, I. A. Mahatma (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This study aims to determine the components of the cost of the processing Arabica coffee in wet and dry, to calculate the cost of Arabica coffee processing in wet and dry and to calculate the value -added processing Arabica coffee in the wet and dry. Data collection methods were nonparticipant observation, questionnaires and documentation. Sampling was set at 27 samples. Data processing method used was the grouping of coffee processing cost components, calculate the total cost of processing coffee, rice coffee reduction sale value and the average cost of processing coffee. The results showed that the cost components in the wet coffee processing were raw materials, water, labor, coffee processing machines, and ancillary equipment. Cost components in the dry coffee processing were raw materials, labor, coffee processing machines, and ancillary equipment . Cost of the wet Arabica coffee processing was Rp7340.89/Kg and cost of the dry Arabica coffee processing was Rp4271.58/Kg. The added value of Arabica coffee in the wet processing was Rp770.22/Kg and dry processing was Rp18.59/Kg which means that the wet coffee processing more profitable for farmers.
Keywords: 32